2012
DOI: 10.5006/0444
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Study of Solids Deposition in Heavy Oil Transmission Pipeline

Abstract: Previous studies have shown that transmission-quality heavy crude oil carries water-wetted solid particles, that these particles can accumulate on the pipe floor and cause under-deposit corrosion, and that the incidence of accumulation is strongly correlated to locations downstream of over-bends. This paper describes a computational fluid dynamics (CFD) analysis of light and heavy oil flow in a representative segment of a real transmission pipeline in which corrosion has been observed. The purpose was to gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…work from Landry et al (2012) suggested that the settlement of solid particles is much easier onto the pipeline bottom and water may also be accumulated around such solid particles forming a locally water-rich environment. In this condition, corrosion may be preferentially initiated around the solid particle (Han et al, 2013).…”
Section: Figure 4 | (A)mentioning
confidence: 99%
“…work from Landry et al (2012) suggested that the settlement of solid particles is much easier onto the pipeline bottom and water may also be accumulated around such solid particles forming a locally water-rich environment. In this condition, corrosion may be preferentially initiated around the solid particle (Han et al, 2013).…”
Section: Figure 4 | (A)mentioning
confidence: 99%
“…Although studies have been conducted to understand how deposits form in order to mitigate deposit formation [1][2] and to experiment with inhibitor packages to understand the risk and mechanisms involved with inhibition of UDC, 3,7-10 no formal attempt has been made to observe the effects of specific chemical components in an inhibitor package on UDC. The objective of this study was to test individual chemical components used in industrial inhibitor packages against localized UDC.…”
Section: -Mercaptoethanolmentioning
confidence: 99%
“…Experimentation for each inhibitor consisted of 28 d in a 2 L glass cell using API (1) 5L X65 pipeline steel partially covered with 250 μm diameter sand particles. Experimental conditions required purging the specified brine (Table 1) with CO 2 at 1 bar (100 kPa) total pressure while maintaining the solution temperature at 70°C.…”
Section: Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation